Scenario planning for libraries - Giesecke, Joan (American Library Association, 1998)
Scenario planning is a technique with which participants develop a set of scenarios that eventuate in possible future outcomes. Not intended to circumscribe the future, it permits organizations and their staffs to help realize the future for the organization by reacting appropriately to change.